1998
DOI: 10.1161/01.res.83.6.594
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Proto-oncogenes and Gene Mutation of Sarcomeric Proteins in Patients With Hypertrophic Cardiomyopathy

Abstract: Abstract-Several mutations of cardiac ␤-myosin heavy chain (␤-MHC) gene were reported in patients with hypertrophic cardiomyopathy (HCM). Involvement of proto-oncogenes has been shown in the mechanism of experimental cardiac hypertrophy. This study sought to examine the effects of c-H-ras and c-myc expression in the steady-state myocardium on hypertrophic changes and to evaluate the possible interaction between ␤-MHC mutation and proto-oncogene expression in HCM. Endomyocardial biopsy was performed in 17 HCM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 43 publications
3
58
0
1
Order By: Relevance
“…A recent study has shown that enhanced expression of several cellular genes associated with cell size control has been found in HCM patients. Interestingly, cardiomyocyte size was found to be correlated with the expression level of c-H-ras and cMyc [177], suggesting that c-H-ras and c-Myc may play a role in the hypertrophic mechanism in HCM by increasing cardiomyocyte size. This conclusion was further supported by another experiment in which overexpression of ras in cardiomyocytes induces enlarged cardiomyocyte size and cardiac hypertrophy [136].…”
Section: Organ Hypertrophy or Atrophymentioning
confidence: 98%
“…A recent study has shown that enhanced expression of several cellular genes associated with cell size control has been found in HCM patients. Interestingly, cardiomyocyte size was found to be correlated with the expression level of c-H-ras and cMyc [177], suggesting that c-H-ras and c-Myc may play a role in the hypertrophic mechanism in HCM by increasing cardiomyocyte size. This conclusion was further supported by another experiment in which overexpression of ras in cardiomyocytes induces enlarged cardiomyocyte size and cardiac hypertrophy [136].…”
Section: Organ Hypertrophy or Atrophymentioning
confidence: 98%
“…In three independent hematoxylin-eosin-stained sections, the shortest transverse myocyte diameter was measured in 50 nucleated transverse sections of the myocytes in each rat. 17 The percent area of myocardial fibrosis was evaluated in three independent Mallory-Azan-stained sections of each rat. 18 Immunohistostaining for monocytes/macrophages was performed using an antibody against ED1 (Chemicon International, Temecula, CA, USA) and a commercially available detection system (DAKO, Glostrup, Denmark).…”
Section: Morphometry and Immunohistostainingmentioning
confidence: 99%
“…23 The shortest transverse myocyte diameter and the percent area of myocardial fibrosis, respectively, were measured in three independent hematoxylin/eosin-stained sections and Mallory-Azan-stained sections of each rat. 23,24 Macrophages labeled with an antibody for ED-1 (Chemicon International, Temecula, CA, USA) were counted at Â200 magnification in three independent entire cross-sections of each animal. 25 …”
Section: Morphometric Analysis and Immunohistostainingmentioning
confidence: 99%